ANALISIS PAJAK REKLAME DI KOTA PONTIANAK - B21109015, Lusiana (Jurnal Pembangunan dan Pemerataan, 2015)
Pontianak city as the city and the administrative center as well as a growing city, the advertisement tax potential prospects for the future. It is known that the average revenue realization of each object advertisement tax in the city of Pontianak annually almost be said to exceed the targets set by the Regional Government of Pontianak. The purpose of this study was to determine the contribution of the advertisement tax to the Local Revenue Pontianak City 2004-2012 period and to determine what factors that support and hinder the development of advertisement tax contribution in Pontianak. The form of a descriptive study. Sources of data collection the authors used library research and field research, consists of: observation, interviews and questionnaires. The results of the research developments in Pontianak advertisement tax for the period 2004-2012 show considerable growth increases. But still low or small in contributing to regional revenue Pontianak City, with the average - average contribution of 5.05% year during 2004-2012, but significant in the financing of government administration. Advertisement tax that contributes the most to the original income Pontianak City occurred in 2009 by 7, 25% and the lowest was in 2004 amounted to 3.37%. The factors that support the development of advertisement tax contribution in Pontianak based on interviews with the Revenue officer Republic Act No. 28 of 2009 on Regional Taxes and Levies and local regulations, the performance of the apparatus, data base, communications, facilities and infrastructure, factors Pontianak city area and many types of businesses that grow. The factors that hinder the development of this advertisement tax contributions Based on interviews with Revenue Officers are: tax payer compliance and awareness, the number of illegal billboards, rates, unstable economic conditions and the lack of traction on the implementation of the regulation. Factors that favor the development of advertisement tax contribution in Pontianak based on the results of questionnaires to taxpayers is: people's income, population growth, many businesses are growing, strategic location available, the availability of field staff and ownership of infrastructure Revenue. Factors that hinder the development of advertisement tax contribution in Pontianak from the questionnaire on taxpayers, namely: lack of socialization, rates, unsatisfactory services, the complexity of the procedure and the lack of traction on sanctions.